2011
DOI: 10.1128/aem.01239-10
|View full text |Cite
|
Sign up to set email alerts
|

Tetracycline Resistance-Encoding Plasmid from Bacillus sp. Strain #24, Isolated from the Marine Sponge Haliclona simulans

Abstract: Knowledge of the nature of resistance determinants in natural habitats is fundamental to increasing our understanding of the development of antibiotic resistance in clinical settings. Here we provide the first report of a tetracycline resistance-encoding plasmid, pBHS24, from a marine sponge-associated bacterium, Bacillus sp. strain #24, isolated from Haliclona simulans.The increased selection pressure created by the overuse and misuse of antibiotics in clinical and agricultural settings has undoubtedly driven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 23 publications
0
29
0
Order By: Relevance
“…While all three plasmids were 5,031 bp in size, pBSDMV46A had a single-base difference from pSU1 and pDMV2 (which were identical to each other). The pBSDMV46A, pSU1, and pDMV2 sequences were almost identical to those of three recently reported Tc r -encoding mobilizable plasmids, pMA67 (NC_010875) (39), pLS55 (NC_010375) (4), and pBHS24 (HM235948) (46). A detailed comparison of these plasmids, including pSU1, is available in reference 46.…”
Section: Absence Of Tet(l) Tet(k) Tet(m) and Tet(o) Genes In Thesementioning
confidence: 69%
See 1 more Smart Citation
“…While all three plasmids were 5,031 bp in size, pBSDMV46A had a single-base difference from pSU1 and pDMV2 (which were identical to each other). The pBSDMV46A, pSU1, and pDMV2 sequences were almost identical to those of three recently reported Tc r -encoding mobilizable plasmids, pMA67 (NC_010875) (39), pLS55 (NC_010375) (4), and pBHS24 (HM235948) (46). A detailed comparison of these plasmids, including pSU1, is available in reference 46.…”
Section: Absence Of Tet(l) Tet(k) Tet(m) and Tet(o) Genes In Thesementioning
confidence: 69%
“…It is noteworthy that several recent studies reported the isolation of three plasmids almost identical to pSU1 from entirely different ecosystems: pMA67 (NC_010875) from a U.S. honeybee pathogen (39), pLS55 (NC_010375) from an Italian raw milk product (4), and pBHS24 (HM235948) from an Irish marine sponge isolate (46). In contrast to a previous report on the unsuccessful transformation of pMA67 into E. coli TOP10 (a recA mutant) (39), each of the plasmids described in this study was transformable into E. coli TOP10.…”
Section: Tet(l)-carrying Plasmid Persistent In Farm Soilmentioning
confidence: 99%
“…New forms of resistant pathogens may emerge if such genes are transferred from probiotics to pathogens [16]. Many studies have been conducted to identify the antibiotic-resistance genes in Bacillus species [17]- [20].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a tetracyclin resistance gene tet(L) transferable to a Bacillus subtilis was observed in a Bacillus spp. strain isolated from a marine sponge Haliclona simulans (Phelan et al, 2011).…”
Section: Antimicrobial Resistance Among Qps Bacillus Species With Regmentioning
confidence: 99%